DESIGN AND SIMULATION OF POWER FACTOR CORRECTION FOR AC/DC CONVERETER - Amina Mahmoud Shaker; Ali M. Salih; Kais S. Ismail (Journal of Engineering, 2008)
One of the biggest problems in power quality aspects is the harmonic contents in the electrical system. Most of the current harmonics are due to the nonlinear operation of the power converters and arc furnaces . These harmonics cause overheating of the magnetic cores of transformers and motors beside their effect on the torque –speed of the later . These problems have lead to the creation of design standards for purpose of limiting the allowable harmonics on the power lines, and hence to improve the power factor. This paper presents two types of power factor correction (PFC) for single phase AC/DC converter, the Boost converter and the Buck- Boost converter. The output of the Boost converter is fixed (400V , 3kW) while the output of the Buck – Boost converter is variable (150-400V, 3kW-1kW) and due to the discontinuous inductor current mode operation of the Buck mode of the Buck- Boost converter an average charge current control is used in the inner current loop control. From harmonic analysis the two types of converters has less harmonics as compared with the IEC1000-3-2 standards. The Buck Boost converter eliminates the problem of high inrush input current produced by the Boost converter type.